Defining the PTSD Service Dog Intervention: Perceived Importance, Usage, and Symptom Specificity of Psychiatric Service Dogs for Military Veterans - Rodriguez, Kerri E.; LaFollette, Megan R.; Hediger, Karin; Ogata, Niwako; O’Haire, Marguerite E. (Frontiers in Psychology, 2020)
Research suggests that psychiatric service dogs may be an effective complementary treatment option for military veterans with posttraumatic stress disorder (PTSD). Although this practice continues to increase in popularity and research has reached the rigor of clinical trials, the components of the PTSD service dog intervention remain largely undefined. This research aimed to 1) quantify the importance, usage, and PTSD symptom specificity of service dog trained and untrained behaviors, 2) explore how PTSD severity, time since receiving the service dog, and the veteran-dog relationship relate to outcomes, and 3) compare expectations of veterans on the waitlist to experiences of veterans with service dogs. In a cross-sectional design, post-9/11 military veterans with PTSD were recruited from a national service dog provider, including n=134 with a service dog and n=82 on the waitlist. Results showed that the service dog’s trained tasks of calming and interrupting anxiety were perceived as the most important for veterans’ PTSD, the most frequently used in a typical day, and as helping the most PTSD symptoms. Trained tasks were most helpful to the PTSD symptoms of hypervigilance and intrusion, and least helpful towards the symptoms of amnesia and risk-taking. Although all trained tasks were helpful towards PTSD symptoms, veterans rated the service dog’s untrained behaviors on average as more important for their PTSD. After controlling for covariates, there was no relationship between a veteran’s PTSD severity and perceived importance or frequency of task use. However, veterans who reported feeling closer to their service dogs reported using trained tasks more often, and veterans who had their service dogs for longer reported using trained tasks less often. Finally, veterans on the waitlist reported higher expectations regarding task use and importance than described by veterans with a service dog. In conclusion, findings describe the core components of the PTSD service dog intervention by quantifying the use and value of trained and untrained dog behaviors. Overall, this study helps explain the PTSD service dog’s clinically-relevant value while contributing to the scientific understanding of this emerging practice.